2009
DOI: 10.1093/heapol/czp054
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of supervision in a project designed to strengthen supervision of Integrated Management of Childhood Illness in Benin

Abstract: Managers should monitor supervision, understand the evolving influences on supervision, and use their resources and authority to both promote supervision and remove impediments to supervision. Support from leaders can be crucial, thus donors and politicians should help make supervision a true priority. As with front-line clinicians, supervisors are health workers who need support. We emphasize the importance of research to identify effective and affordable strategies for improving supervision frequency and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 16 publications
7
48
0
2
Order By: Relevance
“…A randomized control trial from Benin of health workers trained in Integrated Management of Childhood Illness (IMCI) conducted a per-protocol analysis using a pre-/post-design with non-randomized controls due to slow IMCI implementation (54, 69). Three years after implementation, they found a 27% point difference in children receiving recommended care in intervention compared to control areas with routine supervision and a smaller impact on the proportion of IMCI tasks performed (54, 69). In India, the effect of supportive supervision on immunization providers was measured using a before and after design.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized control trial from Benin of health workers trained in Integrated Management of Childhood Illness (IMCI) conducted a per-protocol analysis using a pre-/post-design with non-randomized controls due to slow IMCI implementation (54, 69). Three years after implementation, they found a 27% point difference in children receiving recommended care in intervention compared to control areas with routine supervision and a smaller impact on the proportion of IMCI tasks performed (54, 69). In India, the effect of supportive supervision on immunization providers was measured using a before and after design.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is amply illustrated in a detailed study in Tanzania, which demonstrated a number of problems, including failure to recognise and treat more than one illness in the same child and inadequate referral for severe illness. Although such can often be corrected with adequate supervision, the difficulties of maintaining regular and high quality supervision of service providers are numerous19: poor coordination, lack of skilled managers, competing priorities, lack of financial incentives and logistical difficulties.…”
Section: Imci Successes and Shortcomingsmentioning
confidence: 99%
“…The implementation and scale-up of the programme itself needs managerial supervision in which the roles and responsibilities of supervisors are integrated into the existing system. In lower-income countries, there are many challenges to sustain initial supervisory efforts at all levels of the health system [63].…”
Section: Supportive Supervisionmentioning
confidence: 99%